Diagnostic Stability in Bipolar Disorder: A Narrative Review. Issue 1 (January 2019) - Cegla-Schvartzman, Fanny B.; Ovejero, Santiago; López-Castroman, Jorge; Baca-García, Enrique
Abstract : Learning objectives: After participating in this activity, learners should be better able to: Evaluate diagnostic stability in bipolar disorder Analyze the factors contributing to diagnostic stability Objective: Diagnostic stability is the degree to which a diagnosis remains unchanged during follow-up. It is an important measure of predictive validity in bipolar disorder (BD). In this study, we review the literature concerning diagnostic stability in BD, analyze the factors contributing to diagnostic stability, and describe the implications of diagnostic boundaries and diagnostic delay. Methods: A comprehensive literature search of MEDLINE and EMBASE databases was conducted, including all studies published from 1980 to 2016, to evaluate the diagnostic stability of BD. Thirty-seven articles were included: 6 focusing mainly on BD, 18 on psychotic disorders, 10 on depression, and 3 on diagnostic stability in psychiatric disorders in general. Data analysis was performed in standardized fashion using a predefined form. Results: Despite a high variability of the methodological approaches taken, an acceptable degree of diagnostic stability was found. The most common criteria for evaluating diagnostic stability were prospective consistency and retrospective consistency. The mean prospective and retrospective consistencies were 77.4% and 67.6%, respectively. A large majority of studies were performed in Europe or in North America (67.5%), compared to 21.6% in Asia and only 10.8% in Africa, Oceania, and South America. Extreme ages, female gender, psychotic symptoms, changes to treatment, substance abuse, and family history of affective disorder have been related to diagnostic instability. Conclusions: Several factors appear to have a negative impact on the diagnostic stability, but the evidence is insufficient to draw any robust conclusions. Nevertheless, despite variable prospective and retrospective consistencies, the overall diagnostic stability is good. Standardized methods need to be used to obtain more accurate assessments of stability. Abstract : Supplemental digital content is available in the text.